Effect of increasing the time between slurry application and first rainfall event on phosphorus concentrations in runoff. (12th August 2021) - O'Rourke, Sharon M.; Foy, Robert H.; Watson, Catherine J.; Gordon, Alan; Higgins, Suzanne; Vadas, Peter A.
Abstract: Minimizing slurry phosphorus (P) losses in runoff requires careful management in the context of both soil P surpluses and changing patterns in rainfall. Increasing the time interval between slurry application and the first rainstorm event is known to reduce P loss in runoff although the risk period for elevated P concentrations in runoff can extend for weeks. This study investigated the impact of increasing the time interval between slurry application and first rainstorm event on P concentrations in runoff. Simulated rainfall (40 mm h −1 ) was applied at 2, 4, 10, 18, 30 and 49 days after dairy slurry was surface‐applied to a grassland sward in Ireland. Increasing time to runoff resulted in a decrease in dissolved reactive P concentrations from 5.0 to 1.0 mg P L −1 and a P signal in runoff for 18 days. Beyond 18 days, elevated P concentrations were observed in runoff collected from natural rainfall that preceded the day 49 rainstorm event. A published surface phosphorus and runoff model (SurPhos) was used to understand the slurry P dynamics controlling P interactions with runoff. Dissolved reactive P in runoff was predicted with accuracy by SurPhos, R 2  = .89. The SurPhos model implied that slurry P mineralization occurred during the experimental period that resulted in a small spike in P concentrations beyond the defined risk period. This study shows that the experimental data have the potential to be extrapolated to different weather scenarios using SurPhos and could test when and where slurry P could be most safely spread.